Mengembangkan Keterampilan Sosial Dalam Kehidupan Melalui Model Pembelajaran IPS Di Sekolah Dasar - Rahma Aulia, Lulu; Nuraeni Pebriani, Yulia (Jurnal Penelitian dan Pendidikan IPS, 2023)
Education can be interpreted as a process of forming the character of students and the results of education are indeed to create educated humans and have good character. Basically, social studies learning in elementary school studies theories about social science which aims to shape the personality and character of good Indonesian children. Social studies education is a discipline that is directed at the learning process that teaches students to care about conditions in society and provide solutions to social problems that exist in the surrounding environment. By developing social skills in elementary schools with this learning, students are able to master social skills which include interpersonal skills, collaboration/collaboration skills, interactive communication and global awareness. It is hoped that students will be able to implement this social studies learning in everyday life so that the creation of a good social and national life according to the objectives of social studies learning it self.